MR−Based Molecular Imaging of the Brain: The Next Frontier - de Backer, M.E.; Nabuurs, R.J.A.; van Buchem, M.A.; van der Weerd, L. (American Journal of Neuroradiology, 2010)
SUMMARY: In the foreseeable future, the MI field could greatly assist neuroradiologists. Reporter molecules provide information on specific molecular or cellular events that could not only aid diagnosis but potentially differentiate stages of disorders and treatments. To accomplish this, reporter molecules literally need to pass a barrier, the BBB, which is designed to repel nonessential molecules from the brain. Although this is not a trivial task, several transport systems could be tricked into guiding molecules into the brain. The noninvasive nature in conjunction with a wide availability makes MR imaging particularly suitable for longitudinal neurologic imaging studies. This review explains the principles of MR imaging contrast, delineates different types of reporter molecules, and describes strategies to transport reporters into the brain. It also discusses recent advances in MR imaging hardware, pulse sequences, the development of targeted reporter probes, and future directions of the MR neuroimaging field. ADAlzheimer diseaseBBBblood-brain barrierCAcontrast agentCESTchemical exchange saturation transferCLIOcross-linked iron oxideCNScentral nervous systemDMSOdimethyl sulfoxideEu-DOTAeuropium tetra-azacyclododecane tetraacetic acid18Ffluorine-1819Ffluorine-19FDGfluorodeoxyglucoseGdgadoliniumGd3+gadolinium 3+1H-MR imagingproton MR imagingLRPlysine rich proteinMImolecular imagingMIONmonocrystalline iron oxide nanoparticleMn2+manganese 2+ MRSmagnetic resonance spectroscopyMWmolecular weight31Pphosphorus-31PARACESTchemical exchange saturation transfer using paramagnetic ionsPEGpolyethylene glycolPETpositron-emission tomographyRNAribonucleic acidSPIOsuperparamagnetic iron oxideT1longitudinal relaxation timeT2transverse relaxation time due to spin-spin interactions (irreversible effect)T2*transverse relaxation time due to spin-spin interactions and local inhomogeneities (partly reversible)USPIOultrasmall superparamagnetic iron oxide